Etnobotânica e screening fitoquímico de Sideroxylon Obtusifolium (Roem. & Schult.) T.D. Penn. (Quixabeira), Cabaceiras, Semiárido da Paraíba - Barbosa, Danila de Araújo (2018)
Traditional knowledge can demonstrate both the history of communities and their relationship to local resources. In addition, they provide information that favors the management and management of species, as well as indicate ways of use and preparation that can support phytochemical knowledge. The present study was carried out in the Tapera Community located in the municipality of Cabaceiras, in the Paraíba semi-arid region, in order to record and analyze the traditional uses and knowledge of Sideroxylon obtusifolium (Roem. & Schult.) T.D. Penn. (quixabeira) and its local availability, observing the extractive pressure on it. In addition, considering the main forms (cachaça and water) and part of the plant (bark and leaf) used in the preparation by the community, the presence of secondary metabolites was evaluated through a phytochemical screening. The phytochemical analysis of the bark and the leaves was aimed at evaluating the compounds in both parts and proposing the replacement of the bark use by the leaves, favoring the conservation of the species. Twenty-three family heads (men / women), representing 15.33% of the population, were interviewed and local availability was assessed through a 24-hour GPS-guided trip. The extractive pressure was analyzed by measuring the extractions in the bark of the plant. For the phytochemical screening, leaves and bark of the species were collected for the preparation of extracts based on cachaça, water and alcohol, which were evaluated for the extracted metabolites. The quixabeira is used by Tapera, mainly as medicinal, where the shell is the most cited part and the sauce is the most common form of preparation. A total of 88 trees were recorded, of which 19 showed extraction marks, demonstrating that predatory activities obtained a marked reduction compared to previous data. The leaf and bark extract, made with rum and water, obtained similar results regarding the extraction of the classes of secondary metabolites. In this way, we can suggest quantitative studies in leaves of quixaba, which can demonstrate within the metabolite classes found, which bioactive substances are present, providing the community, through environmental education, another possibility of quixabeira use for medicinal purposes, in order to try to reduce the existing extractive pressure in the species and contribute to its conservation in the environment.